Enhancing Critical Thinking Skills of Children Aged 5–6 Years Through a Project-Based Learning (PjBL) Model - Aprilia Wahyuning Fitri; Septi Rofiqoh (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Makassar, 2025)
This study aims to develop a Project-Based Learning (PjBL) model to enhance critical thinking skills in children aged 5–6 years. The research is based on the urgency of fostering 21st-century skills from early childhood and the limited availability of specific learning models for Early Childhood Education (ECE). Using a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, and Disseminate) by Thiagarajan, Semmel, and Semmel, this study involved expert validators, teachers, and children aged 5–6 years from a ECE institution. The findings revealed that the developed PjBL model and the accompanying teacher guidebook demonstrated high feasibility. Expert validation using Aiken’s V technique produced a high coefficient, indicating strong content validity and internal consistency. Teachers responded positively, stating that the model was easy to understand, relevant, and effective in stimulating children’s critical thinking. The PjBL model integrates syntax, teacher reaction principles, social collaboration systems, and contextual media to promote simple analysis, evaluation, and creation skills. Therefore, it is highly suitable for improving critical thinking in early childhood.